2005
DOI: 10.1055/s-2005-837776
|View full text |Cite
|
Sign up to set email alerts
|

New Estrogenic Prenylflavone fromEpimedium brevicornumInhibits the Growth of Breast Cancer Cells

Abstract: Estrogens maintain female sexual health. The hormone also drives the growth of estrogen receptor (ER) positive breast tumors, and ER modulators, like tamoxifen, are used to reduce tumor recurrence. To identify phytoestrogens with possible health benefits, we screened several Traditional Chinese Medicines and encountered an extract from the leaves of Epimedium brevicornum (EB), with strong (EC50: 1.3 microg/mL) and specific ER-stimulatory activity. It increased estrogen-responsive human breast cancer cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 17 publications
2
52
0
Order By: Relevance
“…15) Similar findings for IcaS have recently been recorded demonstrating that IcaS induced apoptosis by such means as attenuating the HIF-1 protein level in human osteosarcoma cells, 16) suppressing the COX-2/ PGE2 pathway in prostate cancer PC-3 cells, 17) and blocking the STAT3 signaling pathway in U266 multiple myeloma cells. 18) There have also been several reports of other prenylflavonoids derived from Epimedium as an anticancer agent to MCF7 cells, 19,20) Hec1A cells, 21) PC-3 cells, 22) HEPG2 cells, 23,24) SMMC-7721 cells, 25) and SK-Hep-1 cells. 26) However, the paucity of literature y To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…15) Similar findings for IcaS have recently been recorded demonstrating that IcaS induced apoptosis by such means as attenuating the HIF-1 protein level in human osteosarcoma cells, 16) suppressing the COX-2/ PGE2 pathway in prostate cancer PC-3 cells, 17) and blocking the STAT3 signaling pathway in U266 multiple myeloma cells. 18) There have also been several reports of other prenylflavonoids derived from Epimedium as an anticancer agent to MCF7 cells, 19,20) Hec1A cells, 21) PC-3 cells, 22) HEPG2 cells, 23,24) SMMC-7721 cells, 25) and SK-Hep-1 cells. 26) However, the paucity of literature y To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…Herba Epimedii (family Berberidaceae) (known as Yin-Yang-Huo in Chinese) is a famous Chinese herbal medicine. Flavonoids, the effective components contained in the herb, likely exert their estrogen-like (Wang and Lou, 2004) without hyperplastic effects on tumor cells (Yap et al, 2005). The present study demonstrated that the E 2 level was elevated after the administration of Herba Epimedii water extract, indicating that Herba Epimedii might ameliorate the function of ovaries and possess estrogen-like effects.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, the same methanol soluble bioactive agents induce growth promoting effects through the upregulation of epidermal growth factor receptor/mitogen-activated protein kinase signaling pathways in a model of HER-2 + breast cancer (27). Furthermore, organic solvent fractionated extracts from Epimedium brevicornum containing the prenylflavone breviflavone B have been demonstrated to exhibit inhibitory effects on ER-α expression, in addition to on the growth of ER-α + breast cancer cells in vitro and in vivo (28)(29)(30). The growth inhibitory effect of non-fractionated aqueous extract from EG in the present study and the growth modulatory effects of organic solvent fractionated extracts from different Epimedium species in previous studies, suggest that EG has a pleiotropic effect, which is likely due to the presence of distinct constitutive bioactive components.…”
Section: Discussionmentioning
confidence: 99%